Design and develop a UML diagram reader software application (Component Diagram) - Tan, Mick Xiang Hao (2017)
Unified Modelling Languages (UML) diagrams a standard practice and used by many software engineers to describe structures of software systems. These diagrams allow us to document, describe and understand various aspects of a software system in terms of its structure and functionality. Today, there exist a number of platform and software which allows engineers to draft such diagrams. As long as the drafted diagram adheres to the specifications of the UML diagram, engineers will be able to translate the meaning accordingly. As such, engineers may utilize the UML Design Tool of their choice.